Antecedents and consequences of destination brand love – Case Ylläs - Kaisa Aro; Kati Suomi; Saila Saraniemi (Finland, 2022)
A considerable proportion of consumers love things other than people, including brands (Batra, Ahuvia, & Bagozzi, 2012). Brand love is a relatively new concept in academic discussion, and demonstrates the changed relationships between consumers and brands. The area is relevant for study, given the tightening competition in the tourism sector for visitors, funding, and support from different stakeholder groups.
Studies focusing on the relationships between people and places/destinations as brands, are scarce, particularly studies examining consumers’ love for place/destination brands. However, there are two studies focusing on brand love in the context of destination brands: Swanson (2015, 2017) and Lee and Hyun (2016). Thus, understanding on the concept is still limited, in terms of its construct, antecedents, and consequences. Given the current weaknesses in existing knowledge on destination brand love, the purpose of this study is to conceptualize the antecedents and consequences of destination brand love.
roceedings of the Heritage, Tourism and Hospitality International Conference HTHIC 2017